Evaluation of remineralizing potential of Calcium Sucrose Phosphate and CPP-ACP: An in vitro study. Issue 3 (December 2016) - Thabitha Rani, S.; Manjula, M.; Rajendra Reddy, E.; VinayKumar, L.; Ajay Mohan, T.; Sowmya, B.
Abstract: Background: In depth understanding of dental caries progression and improved diagnostic methodologies to assess early demineralization has enabled development of novel remineralizing therapeutics. Hence, an emerging goal of modern dentistry is to manage non-cavitated carious lesions non-invasively through remineralization. Objective: To evaluate the remineralizing potential of Calcium Sucrose Phosphate (CaSP) and Caesine PhosphoPeptide-Amorphous Calcium Phosphate (CPP-ACP) on early enamel lesions. Method: Thirty enamel specimens were prepared from freshly extracted noncarious molars and artificial enamel subsurface lesions were induced. The sample was randomly divided into 3 groups based on the surface treatment i.e. Group A – Control (no surface treatment) Group B – CPP-ACP cream, Group C – CaSP paste. A caries progression test (pH cycling) was carried out for 12 days. All enamel specimens were subjected to quantitative and qualitative analyses at baseline, after demineralization and after remineralisation using Vickers microhardness test and Scanning Electron Microscopy respectively. Results: Statistical analysis using one-way ANOVA followed by multiple comparisons test was applied to detect significant differences at P ≤ 0.05 levels. The mean surface microhardness recovery with CaSP was significantly higher than other groups. Conclusion: The CaSP paste was effective in remineralizing early enamel lesions than CPP-ACP.